Estresses abióticos em híbridos de canola: Efeito do alagamento e de baixas temperaturas - Perboni, Anelise Tessari (2011)
Oilseed rape (Brassica napus L.) belongs to the family Brassicaceae and constitutes the third most produced oilseed in the world, surpassed only by soybean and palm. Flooding of soil and low temperatures can cause alterations in cellular metabolism and impair plant growth, generating a stress condition. Two experiments were conducted using the canola hybrid Hyola 43, Hyola 401, Hyola 420 and Hyola 432. The first was conducted in greenhouse where 10 plants of each hybrid were subjected to stress by flooding for a period of six days. Were evaluated parameters and differences in the kinetics of emission of chlorophyll fluorescence, chlorophyll content, leaf area and dry weight of shoot and root. The flooding caused a reduction of leaf area, root dry mass and root dry mass/shoot dry mass ratio of all hybrids studied. In relation to chlorophyll fluorescence were identified differences in parameters related to specific flows that have undergone changes as a function of stress the latter being more pronounced for Hyola 432. The performace photosynthetic index (PIABS and PIABS,total) showed a decrease after 6 days of the experiment except for hybrid Hyola 420. The analysis of the kinetics of chlorophyll a fluorescence transient showed differential effects of stress application in different sites of photosynthetic apparatus, and these effects were less pronounced in the plants of hybrid Hyola 420. In the second experiment, canola plants were grown in a greenhouse where stress by low temperatures was driven in the Laboratory of Plant Metabolism. Ten plants of each hybrid were placed in a growth chamber the absence of light for different periods of low temperatures: 1 and 4 hours at 0oC and 1, 4 and 15 hours at 4oC. Were evaluated parameters and differences in the kinetics of emission of chlorophyll a fluorescence. The hybrids showed the same behavior in relation to chlorophyll a fluorescence in response to stress by low temperatures. In general, the parameters of chlorophyll fluorescence related to the activity of the PSI were the most affected, and the increase of these parameters resulted in higher values of the PIABS,total. The analysis of the kinetics of chlorophyll a fluorescence transient showed temperature effects, mainly at the J point which reflects the accumulation of reduced plastoquinone (QA -) and the I-P phase reflecting the reduction of end electron acceptors at the PSI acceptor side, ie, ferredoxin (Fd) NADP and other intermediaries. We conclude that the plants of the hibrid Hyola 420 were less affected by flooding showing that this hybrid can be considered less sensitive to stress compared to other hybrids. The parameters that involve the activity of the FSI and the variable fluorescence transient at the J point were more responsive to stress conditions imposed by low temperatures.